Comparison of Intervention Programs to Improve Trunk Stability for Active Females - Kate Schwartzkopf-Phifer; Katie Whetstone; Mark Marchino; Kevin Brown; Kyle Matsel (International Journal of Sports Physical Therapy)
# Background